2003
DOI: 10.1038/sj.hdy.6800239
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the Italian fungi belonging to the taxa Pleurotus eryngii (DC.:Fr.) Quèl and P. ferulae (DC.:Fr.) Quèl

Abstract: A study using allozymes and PCR fingerprinting was conducted to estimate the genetic diversity of Italian populations of two economically important cultivated fungal taxa, Pleurotus eryngii and P. ferulae. Very little is known about the genetic diversity distribution pattern of these taxa. Heterozygote deficiency was observed at few loci; in fact the inbreeding coefficients were not high, which demonstrates that mechanisms restrain the inbreeding act at the local level. Estimates of genetic differentiation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…Thus, based on the above information, the cultivars with these genes might lose resistance when leaves were infected by these pathogen populations in Yunnan Province. The reproduction phase of a pathogen is an important factor considered in studies of pathogen genetic structure (Urbanelli et al 2003). Clonal reproduction allows the most fit individuals to efficiently reproduce quickly and occupy the host.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on the above information, the cultivars with these genes might lose resistance when leaves were infected by these pathogen populations in Yunnan Province. The reproduction phase of a pathogen is an important factor considered in studies of pathogen genetic structure (Urbanelli et al 2003). Clonal reproduction allows the most fit individuals to efficiently reproduce quickly and occupy the host.…”
Section: Discussionmentioning
confidence: 99%
“…Pleurotus eryngii is an edible mushroom with a high commercial value and has been widely cultivated in Europe, Middle East, North America, and Asia (Mandeel et al 2005). The genetic diversity and population structure of P. eryngii have been investigated in several studies (Urbanelli et al 2003(Urbanelli et al , 2007Abdollahzadeh et al 2007;Ro et al 2007;Zervakis et al 2014). However, little is known about the mitochondrial genome of this fungus.…”
mentioning
confidence: 99%
“…Based on 68 best differentiable alleles (Supplementary Material 2) and by dividing the sample set into two populations (five isolates from the Eurasian continent and five isolates from the rest of the world) analysis revealed that most molecular variance occurred within (96.92%), rather than between, populations (3.08%). This is quite a common observation in ubiquitously existing species and especially in sexually reproducing fungi with airborne ascospores [49,50]. Differentiation between populations in our study was detected at only four of the twelve loci (Table 1; L5, L6, L7 and L10) ranging between 2% and 15%.…”
Section: Discussionmentioning
confidence: 78%